Comparison of Methods for Determining Aerobic Exercise Intensity Using Heart Rate in Acute Leukemia Patients Prior to Induction Chemotherapy. (July 2016) - Story, Christina; Bryant, Ashley Leak; Phillips, Brett; Bailey, Charlotte; Shields, Edgar W.; Battaglini, Claudio
Introduction: Cardiopulmonary exercise testing (CPET), the gold standard of cardiopulmonary evaluation, is used to determine VO2 levels at different aerobic exercise training intensities; however, it may not be feasible to conduct CPET in all clinical settings. Aims: To compare the heart rate reserve (HRR) and percent of 220-age methods for prescribing cycle ergometry exercise intensity using heart rate (HR) against the HRs obtained during a CPET in adults undergoing treatment for acute leukemia (AL). Methods: In this exploratory study, part of a larger randomized controlled trial, 14 adults with AL completed CPET on a cycle ergometer with indirect calorimetry within 96 hr of admission to a cancer hospital to determine VO2peak and HR corresponding to low (40% VO2peak ), moderate (60% VO2peak ), and high (75% VO2peak ) exercise intensities. Analyses of variance were used to compare estimated HR for each intensity level using the HRR and percent of 220-age methods with HR determined via VO2peak . Results: HR corresponding to low-intensity exercise differed significantly across all three methods ( p ≤ .05). No significant differences were observed between HR estimated via the percent of 220-age method and determined via VO2peak at moderate (100 ± 8 and 113 ± 24 bpm, p = .122) or high intensities (125 ± 10 and 123 ± 25 bpm, p = .994). Conclusion: In adults with AL, HR-based methods for defining aerobic exercise intensities should be used with caution. At low intensity, neither should be used, while at moderate and high intensities, the percent of 220-age equation might serve as an adequate substitute for CPET.